Penerapan Sistem Pendukung Keputusan Untuk Seleksi Mahasiswa Berprestasi Menggunakan Metode Copras - wendi, al; mandopa, andi saputra (Journal of Advanced Research in Informatics, 2024)
Technological developments are increasingly rapid, students must be able to adapt to changes, be enthusiastic about learning, and care about sustainable development. Therefore, the Independent Campus Learning Policy (MBKM). A Decision Support System (DSS) or Decision Support System (DSS) is a system that is able to provide problem solving capabilities and communication capabilities for problems with semi-structured and unstructured conditions. The COPRAS method or Combination of Ratio Assessment is a multi-criteria decision analysis method used the alternatives involved in a decision. This research aims to obtain ranking results of outstanding students quickly and objectively without requiring a lot of effort. The results of this ranking will help Graha Nusantara Padangsidimpuan University, especially the Faculty of Engineering, Computer Science Study Program, in selecting outstanding students. From the conclusion above, the student selected to be in first place is A3 in the name of Benny Matondang with a score of 99.972 in first place.